Dynamic evolution of ceftazidime–avibactam resistance due to interchanges between blaKPC-2 and blaKPC-145 during treatment of Klebsiella pneumoniae infection - Chen, Yili; Yang, Runshi; Guo, Penghao; Liu, Pingjuan; Deng, Jiankai; Wu, Zhongwen; Wu, Qingping; Huang, Junqi; Liao, Kang (Frontiers in Cellular and Infection Microbiology, 2023)
Background The emergence of ceftazidime–avibactam (CZA) resistance among carbapenem-resistant Klebsiella pneumoniae (CRKP) is of major concern due to limited therapeutic options. Methods In this study, 10 CRKP strains were isolated from different samples of a patient with CRKP infection receiving CZA treatment. Whole-genome sequencing (WGS) and conjugation experiments were performed to determine the transferability of the carbapenem resistance gene. Results This infection began with a KPC-2-producing K. pneumoniae (CZA MIC = 2 μg/mL, imipenem MIC ≥ 16 μg/mL). After 20 days of CZA treatment, the strains switched to the amino acid substitution of T263A caused by a novel KPC-producing gene, blaKPC-145, which restored carbapenem susceptibility but showed CZA resistance (CZA MIC ≥ 256 μg/mL, imipenem MIC = 1 μg/mL). The blaKPC-145 gene was located on a 148,185-bp untransformable IncFII-type plasmid. The subsequent use of carbapenem against KPC-145-producing K. pneumoniae infection led to a reversion of KPC-2 production (CZA MIC = 2 μg/mL, imipenem MIC ≥ 16 μg/mL). WGS analysis showed that all isolates belonged to ST11-KL47, and the number of SNPs was 14. This implied that these blaKPC-positive K. pneumoniae isolates might originate from a single clone and have been colonized for a long time during the 120-day treatment period. Conclusion This is the first report of CZA resistance caused by blaKPC-145, which emerged during the treatment with CZA against blaKPC-2-positive K. pneumoniae-associated infection in China. These findings indicated that routine testing for antibiotic susceptibility and carbapenemase genotype is essential during CZA treatment.